Mild hyperbilirubinaemia as an endogenous mitigator of overweight and obesity: Implications for improved metabolic health. (February 2018) - Seyed Khoei, Nazlisadat; Grindel, Annemarie; Wallner, Marlies; Mölzer, Christine; Doberer, Daniel; Marculescu, Rodrig; Bulmer, Andrew; Wagner, Karl-Heinz
Abstract: Background and aims: Mild endogenous elevation of unconjugated bilirubin (UCB) as seen in Gilbert's syndrome (GS), might mitigate cardiovascular disease (CVD) risk factors including overweight/obesity. This study aimed to determine whether hyperbilirubinaemia is linked to improved anthropometric data and lipid profile. Methods: Our study considered GS and age-/gender-matched healthy controls (n = 248). Additionally, obese female type 2 diabetic patients (DM2) (n = 26) were included as a "disease control group". Results: BMI, hip circumference (HC), and lipid profile were significantly lower in GS. UCB was inversely correlated with BMI ( p <0 .001), HC as well as with fat mass (FM) and lipid variables ( p < 0.05). Moreover, DM2 patients had significantly lower UCB compared to GS and healthy controls. Older GS subjects (≥35 years) had significantly reduced anthropometric data and improved lipid profile. Conclusions: Our results propose that the health promoting potential of mild hyperbilirubinaemia may extend to protection from age-related weight gain and dyslipidaemia. Highlights: Mildly elevated unconjugated bilirubin (UCB) might mitigate cardiovascular disease risk factors including overweight/obesity. Gilbert's syndrome(GS) subjects with mildly elevated UCB were metabolically healthier than age- and gender matched controls. The condition of mild hyperbilirubinaemia (GS) seems to protect from age-related weight gain and dyslipidaemia.